The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/01674820701447447
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of IVF among women: 10 years post-treatment

Abstract: Between 2.1% and 4.2% of all children born in Scandinavian countries are conceived with the help of assisted reproductive technology. The present study is one of the first to have followed up infertile women over a long period. Data on outcomes, satisfaction and the perceived consequences of IVF treatment were collected by means of a questionnaire among a random sample of women (response rate 42%; N = 66) who had undergone IVF at a tertiary referral university hospital in Norway. It was found that 10 years pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…Analyzing long-term outcome of 108 patients referred to one Norwegian IVF center in 1996 and interviewed 10 years later, Sundby et al (13) found an overall success probability of 77%, including 47% of patients who had a child during IVF treatment, 15% who adopted a child, and 15% who had a child after a spontaneous pregnancy. In this Norwegian study, the authors also reported that 13% of patients were bringing up a child (10% as a foster parent and 3% as a stepmother).…”
Section: Discussionmentioning
confidence: 98%
“…Analyzing long-term outcome of 108 patients referred to one Norwegian IVF center in 1996 and interviewed 10 years later, Sundby et al (13) found an overall success probability of 77%, including 47% of patients who had a child during IVF treatment, 15% who adopted a child, and 15% who had a child after a spontaneous pregnancy. In this Norwegian study, the authors also reported that 13% of patients were bringing up a child (10% as a foster parent and 3% as a stepmother).…”
Section: Discussionmentioning
confidence: 98%
“…For many infertile couples, the time between diagnosis, treatment and outcome can be extensive and, if medical treatments are unsuccessful, couples are left to decide if they want to continue treatments, stop treatment, pursue adoption or stay childfree (36)(37)(38). In the study by Sundby et al (39), 56% of the women, who had started fertility treatment 10 years before, had considered divorce, and 17% actually ended the relationship. Furthermore, in some cultures, the concept of voluntary childlessness may not even exist (40).…”
Section: Discussionmentioning
confidence: 99%
“…There were statistically significant differences for depressive, obsessive-compulsive and somatisation symptoms as well as an increased strength of the reported symptoms in the women who had previously undergone IVF treatment. These results are in accordance with those of Gameiro et al (159) in showing that the risk of adverse mental health symptoms can be increased in women many years after infertility treatment (159), but that most women adjust well after infertility treatment, irrespective of its outcome (158,164).…”
Section: Long-term Consequences Of Infertility and Ivf Treatmentsupporting
confidence: 82%
“…Several studies have demonstrated the importance of coping for the long-term psychological consequences of unsuccessful treatment (150,(157)(158)(159)163). Gameiro et al (164) found that most women had adjusted well emotionally 2.5 years after treatment, but that 37% showed evidence of emotional maladjustment and that, 11-17 years after treatment, 1 in 10 women showed no evidence of recovery (164).…”
Section: The Second Decadementioning
confidence: 99%
See 1 more Smart Citation